Dual Colorimetric Sensor for Hg2+/Pb2+ and an Efficient Catalyst Based on Silver Nanoparticles Mediating by the Root Extract of Bistorta amplexicaulis - Ahmed, Farid; Kabir, Humaira; Xiong, Hai (Frontiers in Chemistry, 2020)
Environmental pollution derivated from toxic metals and organic toxins is becoming a serious issue worldwide because of their harmful effects on the ecosystem and human health. Here we are reporting an extremely selective and cost-effective colorimetric sensor for simultaneous recognition of Hg 2+ and Pb 2+ by using green synthesized silver nanoparticles (AgNPs) mediated from the environmental friendly roots extract of Bistorta amplexicalius. Biogenic synthesized AgNPs were well characterized by various spectroscopic techniques e.g. UV-vis, FT-IR, XRD, AFM, and Zetasizer. The photophysical potential of synthesized AgNPs towards common metal cations was explored via absorption spectroscopy and colorimetric assay. The hypsochromic shift in the SPR band of AgNPs can easily be detected through naked eyes vision from dark brown to light yellow in the case of Hg 2+ . A substantial reduction in the absorbance of AgNPs was recorded upon mixing with Pb 2+ . AgNPs based colorimetric sensor is highly sensitive towards Hg 2+ and Pb 2+ with a limit of detection (LOD) of 8.0×10-7 M and 2.0×10 -7 M for Hg 2+ and Pb 2+ respectively. Furthermore, AgNPs showed promising catalytic activity for the degradation of methyl orange dye. These results demonstrate that Bistorta amplexicalius stabilized silver nanoparticles have potential applications as a colorimetric sensor and an effective catalyst for the degradation of methyl orange.